A pairwise/sandwich-like assembly consisting of a TaO3 nanomesh and reduced graphene oxide for a pelletized self-supported cathode towards high-areal-capacity Li–S batteries. Issue 48 (24th November 2022) - Wang, Chenhui; Sakai, Nobuyuki; Ebina, Yasuo; Suehara, Shigeru; Kikuchi, Takayuki; Tang, Daiming; Ma, Renzhi; Sasaki, Takayoshi
Abstract : A pelletized self-supported cathode based on a pairwise/sandwich-like assembly of a TaO3 nanomesh and reduced graphene oxide for high-areal-capacity Li–S batteries. Abstract : Lithium–sulfur (Li–S) batteries have attracted considerable attention as a promising energy storage technology. However, the low loading and utilization of sulfur result in the poor practical energy density of these batteries, which has hindered their extensive application. Herein, we demonstrate the fabrication of a molecular pairwise/sandwich-like assembly of TaO3 /rGO, which can be pelletized into a self-supported cathode to improve sulfur loading and utilization. This unique pairwise/sandwich-like heterostructure of TaO3 /rGO was produced through a solution process via self-assembly and identified by X-ray diffraction analysis/simulation and TEM observations. The molecular-scale heterostructure maximizes attractive features of the TaO3 nanomesh: crystalline open channels, polar Ta–O bonds, Lewis acid surfaces and largely exposed active sites, by combining with electrically conductive rGO. As a result, the heterostructure exhibited fast Li + transfer, effective confinement of polysulfides and high catalytic activity for the conversion of lithium polysulfides and uniform deposition of Li2 S, thereby contributing to high sulfur utilization. Consequently, the Li–S batteries assembled with these self-supported cathodes achieved a high areal capacity of 10.5 mA h cm −2 at 2 mA cm −2 . This versatile strategy of fabricating electrodes with a high loading of powder-like active materials can be applied to various energy storage systems, such as alkali metal batteries, promoting their practical application.